2014
DOI: 10.1142/s0192415x1450013x
|View full text |Cite
|
Sign up to set email alerts
|

Red Cabbage (Brassica oleraceaL.) Mediates Redox-Sensitive Amelioration of Dyslipidemia and Hepatic Injury Induced by Exogenous Cholesterol Administration

Abstract: The widely used culinary vegetable, red cabbage (Brassica oleracea L. Var. capitata f. rubra), of the Brassicaceae family contains biologically potent anthocyanins and a myriad of antioxidants. Previous studies have shown that the pharmacological effects of red cabbage in vivo are redox-sensitive. The present study explored whether red cabbage modulates various histopathological and biochemical parameters in rats administered with a cholesterol-rich diet (CRD). To this end, prolonged administration of a lyophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…an endogenous antioxidant enzyme. Besides, these vegetables are also considered as a rich source of dietary fiber, phytoceutics and antioxidant vitamins (Vallejo et al, 2004;Podsędek et al, 2006;Jeffery and Araya, 2009;Amnah, 2013;Al-Dosari, 2014;Park et al, 2014;Abbas et al, 2017). Furthermore, previous researchers disclosed the mineral profile of raw and cooked common cabbage that reflected higher amounts of potassium followed by calcium, magnesium and sodium, whereas trace amounts of iron, manganese, copper and zinc were also detected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…an endogenous antioxidant enzyme. Besides, these vegetables are also considered as a rich source of dietary fiber, phytoceutics and antioxidant vitamins (Vallejo et al, 2004;Podsędek et al, 2006;Jeffery and Araya, 2009;Amnah, 2013;Al-Dosari, 2014;Park et al, 2014;Abbas et al, 2017). Furthermore, previous researchers disclosed the mineral profile of raw and cooked common cabbage that reflected higher amounts of potassium followed by calcium, magnesium and sodium, whereas trace amounts of iron, manganese, copper and zinc were also detected.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are also in corroboration with the results of the instant study. Mostly in dieting programs, cabbage is given a major share in the diet plan being low in calories(Al-Dosari, 2014). The calories content in brassica vegetables as reported byHeimler et al…”
mentioning
confidence: 98%
“…Specifically, it is used to alleviate symptoms associated with gastrointestinal disorders (gastritis, peptic ulcers, and irritable bowel syndrome) and idiopathic cephalalgia as well as treat injuries [ 15 ]. Growing evidence indicates that cabbage has pharmacological activities against various diseases, including liver cirrhosis, hepatitis, cancer, and hypocholesterolemia [ 16 19 ]. A recent study demonstrated that cabbage prevents pancreatitis and identified six bioactive compounds, including several flavonoids, by gas chromatography-mass spectrometry analysis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study evaluated the cytoprotective effect of an RCB aqueous extract at concentrations of 0.005, 0.050, and 0.25 mg/ml in human HepG2 cells, using an assay based on 2,7‐dichlorofluorescein (DFC) (toxic agent). The results revealed that RCB extract reduced the DFC‐induced damage by 25% to 250 mg/ml, a significant hepatoprotective effect ( p < 0.05) compared to the DFC control (Al‐Dosari, 2014). Based on the above data, phenolic acids, flavonoids, anthocyanins, and fiber present in cabbage varieties are the main bioactive compounds that contribute mainly to amylolytic enzymes inhibition responsible for carbohydrates into sugars conversion.…”
Section: Antidiabetic Effects Of Cabbage Varieties At In Vitro In Vivo and Clinical Studiesmentioning
confidence: 94%